Pengaruh Kualitas Aparatur Melalui SIMDA dan Sistem Pengendalian Internal Terhadap Pencegahan Fraud Pengelolaan BMD - Fahrurrozi, Handia; Akram, Akram; Basuki, Prayitno (E-Jurnal Akuntansi, 2019)
Changes in organizational structure result in the transfer of assets with potential fraud. Prevention is one of the long-term solutions to minimize fraud. This study aims to provide empirical evidence of the influence of the quality of government apparatus, the role of SIMDA and the internal control system on preventing fraud in the management of regional property. The population of the study was the management of goods and ASN in the field of management of BMD totaling 128 people. The sample selection uses purposive sampling with a total of 80 people. The results showed that the quality of the apparatus and SIMDA both directly and indirectly did not affect the prevention of fraud in managing regional property. Whereas, the internal control system influences fraud prevention. The implications of this research can be used as input material for regional governments in developing programs and fraud prevention actions for regional property management. Keyword: Quality of apparatus; SIMDA; internal control system; fraud prevention.